Practice of the nurses in breastfeeding-friendly units of basic health - Felipe César Stabnow Santos; Ana Cristina Teixeira Cyrino; Floriacy Stabnow Santos; Marcelino Santos Neto; Fabiana Nara Ambrósio Abrahão (Universidade Federal do Ceará, 2014)
The Breastfeeding-Friendly Basic Units Initiative is a tool that helps to encourage breastfeeding. This study aimed at describing the nurses' knowledge on the Ten Steps of the Breastfeeding-Friendly Basic Units Initiative, as well as verifying educational activities and encouraging the breastfeeding promoted by nurses, assessing the same opinion about their own care and factors that hinder the improvement of service. Descriptive study with a quantitative approach. We interviewed 20 health professionals in Anapolis, GO, Brazil. The results showed that most nurses received training on breastfeeding, however, the number of lectures, individual and group meetings held to publicize the issue were insufficient. The Ten Steps of the Breastfeeding-Friendly Basic Units Initiative were not known by the majority, who were dissatisfied with the governmental incentives. Nurses must develop actions to promote and support breastfeeding.